Luminopsins integrate opto- and chemogenetics by using physical and biological light sources for opsin activation - Berglund, Ken (2016)
Luminopsins are fusion proteins of luciferase and opsin that allow interrogation of neuronal circuits at different temporal and spatial resolutions by choosing either extrinsic physical or intrinsic biological light for its activation. Building on previous development of fusions of wild-type Gaussia luciferase with channelrhodopsin, here we expanded the utility of luminopsins by fusing bright Gaussia luciferase variants with either channelrhodopsin to excite neurons (luminescent opsin, LMO) or a proton pump to inhibit neurons (inhibitory LMO, iLMO). These improved LMOs could reliably activate or silence neurons in vitro and in vivo. Expression of the improved LMO in hippocampal circuits not only enabled mapping of synaptic activation of CA1 neurons with fine spatiotemporal resolution but also could drive rhythmic circuit excitation over a large spatiotemporal scale. Furthermore, virus-mediated expression of either LMO or iLMO in the substantia nigra in vivo produced not only the expected bidirectional control of single unit activity but also opposing effects on circling behavior in response to systemic injection of a luciferase substrate. Thus, although preserving the ability to be activated by external light sources, LMOs expand the use of optogenetics by making the same opsins accessible to noninvasive, chemogenetic control, thereby allowing the same probe to manipulate neuronal activity over a range of spatial and temporal scales.